Streptococcus agalactiae Meningitis in Adult Patient: A Case Report and Literature Review - Fahmi Yousef Khan (Case Reports in Infectious Diseases)
We report a case of group B streptococcus meningitis in a 72-year-old female patient who was admitted in our hospital with a 21-day history of bilateral lower thigh pain and swelling associated with fever, headache, and vomiting. Her past medical history was remarkable for DM type 2, hypertension, and hypothyroidism. Upon admission, examination showed bilateral warmth and tender soft tissue swelling around the knees and MRI showed cellulitis of distal thirds of both thighs. The next day, the patient became drowsy. Neurologic examination showed neck rigidity and right sided hemiparesis. Cerebrospinal fluid and blood cultures yielded group B streptococcus sensitive to ceftriaxone, penicillin G, and vancomycin. The patient received ceftriaxone for a total of 14 days after which she improved and was discharged from the hospital with right sided weakness.